Pengaruh Perceived Usefulness, Perceived Ease Of Use Dan Trust Terhadap Kepuasan Pengguna Qris Bagi Pelaku Usaha Umkm Kab. Bekasi - Mika Evanggelina Manurung; Prasetyo Harisandi; Adibah Yahya (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The purpose of this study was to determine the effect of perceived usability, perceived ease of use, and trust on Qris user satisfaction for MSMEs in Bekasi Regency. The population in this study were MSMEs in Bekasi Regency. Data collection used a questionnaire, using a Likert scale. This study took 100 respondents. The data analysis used was the validity and reliability test of the instrument, the classical assumption test, the multiple linear regression analysis test, the hypothesis test, and the coefficient of determination test. The data processing tool used Smart Pls version 4 for Windows. The results of this study indicate that perceived ease of use has an effect on user satisfaction. Perceived usefulness has no effect on user satisfaction. Trust has an effect on user satisfaction. And together perceived usefulness, perceived ease of use, and trust have an effect on user satisfaction